The key role of shared participation in changing occupational self‐efficacy through stress management courses. Issue 3 (7th May 2015) - Füllemann, Désirée; Jenny, Gregor J.; Brauchli, Rebecca; Bauer, Georg F.; Michel, Alexandra; O'Shea, Deirdre; Hoppe, Annekatrin
<x xml:space="preserve">Abstract</x> This study is the first that longitudinally examined change in occupational self‐efficacy (OSE) through individual and shared participation in occupational stress management courses (SMC). Applying the framework of social cognitive theory (Bandura, 1986, Social foundations of thought and action: A social cognitive theory. Englewood Cliffs, NJ: Prentice‐Hall), we assumed that participation in SMC facilitates OSE perceptions. We further assumed that the psychosocial environment promotes change in OSE through high shared participation (reach) in SMC within work groups. Comparing participants and non‐participants, we conducted growth analyses with three waves of data nested in n = 545 employees further nested in 97 work groups. The results showed that individual participation in SMC alone was insufficient to enhance OSE, a combination of individual and high shared participation being needed to significantly enhance OSE perceptions over a period of 2 years. The results are discussed with reference to specificity issues and the role of the psychosocial environment by applying social identity theory and the notion of shared mental models. We conclude by recommending SMC as a feasible intervention to enhance OSE in heterogeneous occupational contexts – if a majority of work group members can be involved. Practitioner points The study recommends stress management courses for enhancing occupational self‐efficacy as a short and relatively low‐cost intervention that is feasible to implement in various occupational and organizational contexts. The key point here is that a majority of work group members are encouraged to engage in courses to obtain the beneficial effects on change in occupational self‐efficacy.